Development of Local Potential Booklet Mangrove Mangunharjo Ecosystem to Improve Environmental Literacy - Sianturi, Amri; Sigit Saptono; Margareta Rahayuningsih (Journal of Innovative Science Education, 2024)
Using local potentials as a source of teaching materials in the biology learning process affects building contextual learning and stimulating learners to learn more about the surrounding environment. Mangrove Mangunharjo ecosystem can be used as a learning resource to improve students' knowledge of the environment. The purpose of this study is to develop a booklet on the local potential of the mangrove Mangunharjo ecosystem Semarang as an effort to improve environmental literacy. Research methods using R&D with the ADDIE model. The booklet was implemented using a quasi-experiment. The results showed that: 1) The mangrove Mangunharjo ecosystem has the potential to serve as a learning resource. 2) The characteristics of the booklet contain specific information about ecosystem materials that utilize the local potential of mangrove Mangunharjo, which is used as a learning resource. 3) The validity of the booklet obtained a result score from material experts of 92.1% with a very valid category and a result score from media experts of 97.2% with a very valid category. 4) The effectiveness of the booklet on students' environmental literacy obtains the result of N-gain analysis is known that the value of N-gain in the experimental class is much higher with the value of N-gain of 0.536 with moderate criteria, while the value of N-gain in the control class of 0.352 with moderate criteria. Based on developing the ecosystem booklet, mangrove Mangunharjo was declared feasible based on validity, readability, practicality, and effectiveness as a learning resource.